Military trade unions: A threat to national security …. Really? - Heinecken, Lindy (Scientia Militaria - South African Journal of Military Studies, 2017)
The opinion piece by Eric Z. Mnisi claiming that national security has been sacrificed at the altar of soldiers’ Constitutional rights to form and join trade unions is a claim often muted, not only in South Africa. In the Handbook on Human Rights and Fundamental Freedoms of Armed Forces Personnel it is stated that “unionization of military personnel is seen as conflicting with the unique nature of the military and its role in maintaining national security and public order”